CHARACTER EDUCATION IN REALIZING HUMAN POTENTIAL WITH NOBLE MORALS - Miftachul Amri (Adisam Publisher, 2024)
This literature review aims to look at character education in realizing human potential with noble morals. Character education aims to improve the quality of implementation and educational outcomes that lead to the achievement of the formation of character or noble morals in a complete, integrated and balanced manner, in accordance with graduate competency standards. Through character education it is hoped that they will be able to independently improve and use their knowledge, study and internalize and personalize values. -character values and noble morals so that they are manifested in everyday behavior. Character formation and character education starts at home, through school, and in everyday life in society, thus, it cannot be done solely through learning knowledge, but must also be done through instilling or educating values. The formation of human morals in their consciousness is supported by the potential of reason or ratio which drives the selectivity of good or bad actions. Then, humans also have the potential for feeling which they achieve through their visual senses and emotional strength in their souls, thereby developing their intuitive ability to adopt something they judge to be good and beneficial.